Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity - Kilpeläinen, Tuomas O.; Jonas, Jost B. (Nature Communications, 2019)
GWAS have identified more than 500 genetic loci associated with blood lipid levels. Here, the authors report a genome-wide analysis of interactions between genetic markers and physical activity, and find that physical activity modifies the effects of four genetic loci on HDL or LDL cholesterol.